The Effectiveness of Social Story in Reducing Impulsive-Obsessive Behavior in Grade VIII Children with Autism Spectrum Disorder - Hartanti, Dwi Anggraini (Universitas Sultan Ageng Tirtayasa, 2025)
Abstrak: This study examines The effectiveness of Social Story in reducing of obsessive-impulsive behavior, specially excessive greeting, in eight-grade student with Autism Spectrum Disorder (ASD). Using single-subject A-B-A-B design, the intervention was conducted over four weeks, involving baseline, two intervention phases, and reversal. The participant, a 15 year old student referred to as JAmie, displayed repetitive social behavior that was contextually inappropriate. Data were collected through direct daily observation using frequency recording. Results indicated a significant reduction in the target behavior during intervention phases, from 6.6 instances per day in the initial baseline to 3.2 during both intervention, with rise to 5.8 during reversal. These finding suggest that Social Story is an effective behavioral support strategy to improve social understanding and impulse regulation in adolescents and recommends the use of Social Story as part of inclusive behavioral intervention in school settings.